LEARNING STYLES AND STYLES OF COPING WITH STRESS IN UNIVERSITY ENGINEERING STUDENTS (Proceedings of the International Conference on Education, 2021)
The present research has been developed in the university environment. The objective was to determine the relationship between Learning styles and styles of coping with stress in university chemical engineering students of the National University of Callao. Regarding the methodology, it can be pointed out that the type of research is applicative, with a quantitative approach and descriptive correlational level, regarding the sample, the study was represented by 273 engineering students of a public university of Peru - Callao. For this purpose, the Carver's Stress Coping Modes Questionnaire and the Honey and Alonso's Learning Styles Questionnaire were administered. Then, the data were systematized and the inferential statistical analysis was carried out for hypothesis testing, using Pearson's Correlation statistic and the homogeneity of variances test. In addition, the validation of the instruments was established through Cronbach's Alpha, having a reliability index of 0.70. In this regard, the results indicate a significant relationship between all learning styles and styles of coping with stress in the university students evaluated. That is, between the active learning style and emotion-focused and additional styles of coping with stress; between the reflective learning style and problem-focused styles of coping with stress; between the theoretical learning style and problem-focused and emotion-focused style of coping with stress; and between the pragmatic learning style and emotion-focused style of coping with stress.
Keywords: learning styles; coping; stress; university engineering students